Stem cell aging in adult progeria. Issue 1 (December 2015) - Cheung, Hoi-Hung; Pei, Duanqing; Chan, Wai-Yee
Abstract Aging is considered an irreversible biological process and also a major risk factor for a spectrum of geriatric diseases. Advanced age-related decline in physiological functions, such as neurodegeneration, development of cardiovascular disease, endocrine and metabolic dysfunction, and neoplastic transformation, has become the focus in aging research. Natural aging is not regarded as a programmed process. However, accelerated aging due to inherited genetic defects in patients of progeria is programmed and resembles many aspects of natural aging. Among several premature aging syndromes, Werner syndrome (WS) and Hutchinson–Gilford progeria syndrome (HGPS) are two broadly investigated diseases. In this review, we discuss how stem cell aging in WS helps us understand the biology of aging. We also discuss briefly how the altered epigenetic landscape in aged cells can be reversed to a "juvenile" state. Lastly, we explore the potential application of the latest genomic editing technique for stem cell-based therapy and regenerative medicine in the context of aging.